Ibrutinib for Hospitalized Adults With Severe Coronavirus Disease 2019 Infection: Results of the Randomized, Double-Blind, Placebo-Controlled iNSPIRE Study. (24th March 2022) - Coutre, Steven E; Barnett, Christopher; Osiyemi, Olayemi; Hoda, Daanish; Ramgopal, Moti; Fort, Alexander C; Qaqish, Roula; Hu, Yiran; Ninomoto, Joi; Alami, Negar N; Styles, Lori; Treon, Steven P
Abstract: Background: Few therapies are approved for hospitalized patients with severe coronavirus disease 2019 (COVID-19). Ibrutinib, a once-daily Bruton tyrosine kinase inhibitor, may mitigate COVID-19–induced lung damage by reducing inflammatory cytokines. The multicenter, randomized, double-blind phase 2 iNSPIRE study evaluated ibrutinib for prevention of respiratory failure in hospitalized patients with severe COVID-19. Methods: Adult patients with severe COVID-19 requiring hospitalization and supplemental oxygen but without respiratory failure were randomized 1:1 (stratified by remdesivir prescription) to ibrutinib 420 mg or placebo once daily for up to 28 days plus standard of care (SOC), including remdesivir and/or dexamethasone. Results: Forty-six patients were randomized to ibrutinib plus SOC (n = 22) or placebo plus SOC (n = 24). The primary endpoint (proportion of patients alive and without respiratory failure through day 28) was not met, with no statistically significant difference adjusting for remdesivir prescription (86% with ibrutinib plus SOC vs 79% with placebo plus SOC; adjusted difference, 5.8% [80% confidence interval, –9.2% to 20.4%]; P  = .599). Secondary endpoints also showed no statistically significant improvement with ibrutinib plus SOC. Median treatment duration was 14 days for ibrutinib and placebo. Adverse events were similar with ibrutinib plus SOC vs placebo plus SOC (overall: 55% vs 50%; serious: 18% vs 13%) and were consistent with the known safety profile of ibrutinib. Conclusions: Addition of ibrutinib to SOC did not improve the proportion of patients alive and without respiratory failure through day 28 in hospitalized patients with severe COVID-19. Ibrutinib had a manageable safety profile, with similar safety to placebo. Clinical Trials Registration: NCT04375397. Abstract : Ibrutinib had a manageable safety profile but did not improve the proportion of patients alive and without respiratory failure through day 28 vs placebo in hospitalized patients with severe COVID-19 also receiving supportive standard of care, including remdesivir and/or dexamethasone.